Single fibre cytoarchitecture in ventilator-induced diaphragm dysfunction (VIDD) assessed by quantitative morphometry second harmonic generation imaging: Positive effects of BGP-15 chaperone co-inducer and VBP-15 dissociative corticosteroid treatment - Mnuskina, Sofia; Bauer, Julian; Wirth-Hücking, Anette; Schneidereit, Dominik; Nübler, Stefanie; Ritter, Paul; Cacciani, Nicola; Li, Meishan; Larsson, Lars; Friedrich, Oliver (Frontiers in Physiology, 2023)
Ventilator-induced diaphragm dysfunction (VIDD) is a common sequela of intensive care unit (ICU) treatment requiring mechanical ventilation (MV) and neuromuscular blockade (NMBA). It is characterised by diaphragm weakness, prolonged respirator weaning and adverse outcomes. Dissociative glucocorticoids (e.g. vamorolone, VBP-15) and chaperone co-inducers (e.g. BGP-15) previously showed positive effects in an ICU-rat model. In limb muscle critical illness myopathy, preferential myosin loss prevails, while myofibrillar protein post-translational modifications are more dominant in VIDD. It is not known whether the marked decline in specific force (force normalised to cross-sectional area) is a pure consequence of altered contractility signaling or whether diaphragm weakness also has a structural correlate through sterical remodeling of myofibrillar cytoarchitecture, how quickly it develops, and to which extent VBP-15 or BGP-15 may specifically recover myofibrillar geometry. To address these questions, we performed label-free multiphoton Second Harmonic Generation (SHG) imaging followed by quantitative morphometry in single diaphragm muscle fibres from healthy rats subjected to five or ten days of MV+NMBA to simulate ICU treatment without underlying confounding pathology (like sepsis). Rats received daily treatment of either Prednisolone, VBP-15, BGP-15 or none. Myosin-II SHG signal intensities, fibre diameters (FD) as well as the parameters of myofibrillar angular parallelism (cosine angle sum, CAS) and in-register of adjacent myofibrils (Vernier density, VD) were computed from SHG images. ICU treatment caused a decline in FD at day 10 as well as a significant decline in CAS and VD from day 5. Vamorolone effectively recovered FD at day 10, while BGP-15 was more effective at day 5. BGP-15 was more effective than VBP-15 in recovering CAS at day 10 although not to control levels. In-register VD levels were restored at day 10 by both compounds. Our study is the first to provide quantitative insights into VIDD-related myofibrillar remodeling unravelled by SHG imaging, suggesting that both VBP-15 and BGP-15 can effectively ameliorate the structure-related dysfunction in VIDD.